Orophea phouphamarnensis (Annonaceae), a new species from limestone karst in central Laos - Kongxaisavath, Deuanta; Tagane, Shuichiro; Souvannakhoummane, Keooudone; Phengmala, Kajonesuk; Sengthong, Anousone; Dang, Van-Son; Nguyen, Quoc Bao; Yamamoto, Takenori; Tanaka, Nobuyuki; Takahashi, Kotaro T.; Souladeth, Phetlasy (Phytotaxa, 2025)
In Southeast Asia, approximately 408,000 km2 is covered with limestone, most of which was originally fragmented in distribution (Clements et al. 2006). In Laos, the limestone area is about 30,000 km2, covering ca. 12.6% of land in northern and central Laos. Khammouane Province, central Laos, is one of the core sites of limestone in the country where two main national protected areas, Phou Hin Poun National Protected Area and Hin Nam No National Park, are well known. In addition, the Nam Sanam-Phou Pha Marn Provincial Protected Area (hereafter PPA) covers an area of about 1,500 km2, in which the Rock Viewpoint Phou Pha Marn covers a huge area of the PPA.